Barrett's Esophagus in Romania: what do we know? - Piloiu Claudia; Dumitrascu Dan L. (Sciendo, 2020)
Background and aims. The incidence of Barrett's Esophagus (BE) is increasing worldwide, thus diagnosis is becoming a major key of interest in preventing esophageal adenocarcinoma. Because the status of BE in Romania is unclear, we performed a narrative review to comprehensively evaluate all published articles on BE from Romania.